2019
DOI: 10.1111/jch.13557
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of perindopril‐amlodipine vs perindopril‐indapamide on blood pressure control in sub‐Saharan type 2 diabetic individuals newly diagnosed for hypertension: A double‐blinded randomized controlled trial

Abstract: Poor blood pressure (BP) control contributes to complications in sub‐Saharan African (SSA) type 2 diabetic individuals. Experts have advocated the use of combination therapies for effective BP control in these patients. The suggested combinations should include a RAAS antagonist and either a CCB or a thiazide diuretic; however, their efficacy is yet to be established in SSA. We investigated the short‐term effects of two combination therapies on BP control in SSA type 2 diabetic individuals. This was a double‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In people living with diabetes, the risk of developing CVD and life-threatening complications is determined by the degree of control of hypertension. However, hypertension is often inadequately controlled, and the cardiovascular complications in SSA diabetic individuals are attributed to suboptimal blood pressure control [ 26 , 62 ]. Nevertheless, there is a paucity of data on the pooled prevalence and associated factors of suboptimal blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In people living with diabetes, the risk of developing CVD and life-threatening complications is determined by the degree of control of hypertension. However, hypertension is often inadequately controlled, and the cardiovascular complications in SSA diabetic individuals are attributed to suboptimal blood pressure control [ 26 , 62 ]. Nevertheless, there is a paucity of data on the pooled prevalence and associated factors of suboptimal blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal cohort study of 30,228 diabetic patients, only 43 and 30% of European American and African American diabetic hypertensive patients, respectively, demonstrated a target blood pressure of 130/80 mmHg [ 23 ]. In SSA, rates of BP control range between 11 and 35% [ 24 , 25 ], and the cardiovascular complications in this region diabetic individuals are attributed to the suboptimal blood pressure control [ 26 ]. A study carried out in six specialized diabetes care centers of six SSA showed an overall suboptimal BP control in T2DM individuals despite adherence to guidelines [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In peoples living with diabetes, the risk of developing CVD and life-threatening complications is determined by the degree of control of hypertension. However, the rate of control of hypertension is often inadequate and the cardiovascular complications in SSA diabetic individuals are attributed to poor blood pressure control (14,27,68). This systematic review and meta-analysis estimated the pooled prevalence and associated factors of poor blood pressure control among peoples living with diabetes mellitus in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal cohort study of 30,228 diabetic patients, only 43 and 30% of European American and African American diabetic hypertensive patients, respectively, demonstrated a target blood pressure of 130/80 mmHg (24). In SSA rates of BP control range between 11 and 35% (25,26) and the cardiovascular complications in this region diabetic individuals are attributed to poor blood pressure control (27). A study carried out in six specialized diabetes care centers of six SSA showed an overall poor BP control in T2DM individuals despite adherence to guidelines (26).…”
mentioning
confidence: 96%
“…In this issue of the journal, Sobngwi et al from Yaounde, Cameroon, have published a short‐term efficacy and tolerability study, comparing two single tablet fixed‐dose combination medicines in individuals with type 2 diabetes mellitus and newly diagnosed hypertension.…”
mentioning
confidence: 99%